2006
DOI: 10.1002/j.1556-6978.2006.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Family Systems Theory Through Service‐Learning

Abstract: The authors present a rationale for incorporating service-learning projects into courses that teach family systems theory. A model program is presented to provide an example of the objectives, practical considerations, and student responses to such a project. Recommendations for counselor educators are made based on experience with the model program and student feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…We selected a single-case design because such studies tend to encourage adherence to the process of exploring and understanding the phenomenon under study rather than attempting to identify and account for differences between cases (Maxwell, 2004). Outside of Arman and Scherer (2002) and Murray et al (2006), we found that the research literature on PPSL in counselor education lacks a qualitative investigation of the PPSL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a single-case design because such studies tend to encourage adherence to the process of exploring and understanding the phenomenon under study rather than attempting to identify and account for differences between cases (Maxwell, 2004). Outside of Arman and Scherer (2002) and Murray et al (2006), we found that the research literature on PPSL in counselor education lacks a qualitative investigation of the PPSL.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the counselor education literature indicated that service-learning in counselor preparation is generally conducted before practicum training. This review revealed several examples of prepracticum service-learning (PPSL) in counselor education: providing group play therapy at a community center (Baggerly, 2006), coordinating a scavenger hunt for families of children who have a physical disability (Murray, Lampinen, & Kelley-Soderholm, 2006), and facilitating psychoeducational groups on diversity with high school students (Nikels, Mims, & Mims, 2007).…”
mentioning
confidence: 99%
“…Examples include having students facilitate psychoeducational groups discussing diversity issues within a high school setting (Nikels, Mims, & Mims, 2007), having counseling students observe and/or run group play therapy at a community center (Baggerly, 2006), or having counseling students organize and coordinate a scavenger hunt designed specifically for children who have physical disabilities (Murray, Lampinen, & Kelley-Soderholm, 2006). These types of learning experiences can add a dimension to classroom learning and provide counseling students with opportunities to engage more deeply in the course content.…”
Section: Service-learning and Counselor Educationmentioning
confidence: 99%
“…Service-learning experiences can vary across programs. Examples include having students facilitate psychoeducational groups discussing diversity issues within a high school setting (Nikels, Mims, & Mims, 2007), having counseling students observe and/or run group play therapy at a community center (Baggerly, 2006), or having counseling students organize and coordinate a scavenger hunt designed specifically for children who have physical disabilities (Murray, Lampinen, & Kelley-Soderholm, 2006). These types of learning experiences can add a dimension to classroom learning and provide counseling students with opportunities to engage more deeply in the course content.…”
Section: Service-learning and Counselor Educationmentioning
confidence: 99%